Analysis of E-Learning User Acceptance Factors UPN Veteran Jatim - Arista Pratama; Mochamad Alif Abror; Anita Wulansari (Universitas Bina Darma, 2022)
The utilization of Information and Communication Technology (ICT) has an important role in the field of education during the COVID-19 pandemic. Online learning by utilizing e-learning media is an educational solution for the implementation of learning during pandemics. UPN Veteran Jatim utilizes information and communication technology in teaching and learning by using e-learning (Interactive Learning Management of UPN Jatim). This study aims to analyze the factors that affect user acceptance of UPN Veteran Jatim e-learning . The study used the Unified Theory of Acceptance and Use of Technology (UTAUT) research model. Data sampling was conducted online with a total of 387 respondents. The research data was analyzed using SEM with WarpPLS software. The results showed that performance expectancy, effort expectancy, social influence had a positive and significant effect on students' intentions in using UPN Veteran Jatim e-learning. In addition, facilitating conditions and behavioral intentions also positively affect the behavior of students using UPN Veteran Jatim.